2015
DOI: 10.4314/mmj.v27i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Pathologically confirmed breast cancer in Malawi: a descriptive study: Clinical profile of breast cancer

Abstract: BackgroundBreast cancer is the most common female cancer in Africa, yet no published studies have investigated breast cancer in Malawi. Understanding the clinical profile of breast cancer is important to develop early diagnosis efforts. AimTo describe clinical and pathological characteristics of breast specimens from a pathology laboratory at a national teaching hospital. MethodsSecondary analysis of pathology reports from July 2011 to September 2013. ResultsAmong 85 breast cancer cases, 55% were < 50 years. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 11 publications
4
13
0
Order By: Relevance
“…This is consistent with findings from a review of pathology reports that nearly half of Malawian breast cancer patients experienced multiple symptoms for over 1 year before being diagnosed [29]. Symptom appraisal and cancer knowledge have been cited as factors of delay and cancer behaviors in studies worldwide [8, 9, 13, 20].…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with findings from a review of pathology reports that nearly half of Malawian breast cancer patients experienced multiple symptoms for over 1 year before being diagnosed [29]. Symptom appraisal and cancer knowledge have been cited as factors of delay and cancer behaviors in studies worldwide [8, 9, 13, 20].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, finding many participants who reported prevalent breast symptoms during CBE is consistent with our own prior findings of long symptom durations before breast cancer diagnosis in Malawi and extremely low breast cancer awareness among Malawian women. 23 CBE scale-up in Malawi could partially address symptomatic disease and even non-breast conditions in addition to asymptomatic breast disease. This is illustrated by a patient with Kaposi sarcoma diagnosed through our program and brought into care, health impacts of CBE may be greater in settings like Malawi than high-income countries.…”
Section: 4 Discussionmentioning
confidence: 99%
“…22 Patients are typically diagnosed at late stages with long symptom durations before diagnosis. 23 The Malawi Ministry of Health has prioritized early detection of breast and cervical cancer in the national strategic plan. 24 However, no coordinated breast cancer screening program currently exists.…”
Section: 1 Introductionmentioning
confidence: 99%
“…In Malawi, breast cancer patients are often diagnosed with large tumors more than a year after symptoms initially present [4]. Women face multiple individual, interpersonal, cultural, and system-level barriers which affect access to care and delay diagnosis [5].…”
Section: Introductionmentioning
confidence: 99%